Caffeine-enhanced anti-tumor immune response through decreased expression of PD1 on infiltrated cytotoxic T lymphocytes - Venkata Charan Tej G.N.; Neogi K.; Verma S.S.; Chandra Gupta S.; Nayak P.K. (My University, 2025)
Caffeine (1,3,7-trimethylxanthine) is a naturally occurring, habitually consumed food constituent throughout the world. Prospective cohort studies revealed that caffeine consumption reduces the relative risk of various cancers. Avoiding immune destruction is one of the emerging hallmarks of cancer. One of the immunosuppressive pathways that contribute in avoiding immune destruction by cancer cells is adenosine-A2A receptor pathway. Based on prospective epidemiological and mechanistic preclinical studies of caffeine and its predominant antagonistic effect on A2A receptor, we aimed to investigate the effect of caffeine on T cell infiltration into the tumor and expression of PD-1 receptor on T lymphocytes during tumor initiation and progression in a carcinogen-induced tumor model. Our results demonstrate that caffeine treatment significantly lowered tumor incidence and tumor growth rate. We found that the total T-lymphocyte infiltration and CD8+ T lymphocyte infiltration was significantly increased in caffeine-treated groups. On the other hand, the infiltration of CD4+CD25+ regulatory T lymphocyte was significantly decreased in caffeine-treated groups. In addition, the PD-1 expression on CD8+ T lymphocytes and CD4+CD25+ regulatory T lymphocytes was significantly reduced in caffeine-treated groups. We further investigated whether the observed anti-tumor effect of caffeine is mediated through the release of cytokines. We found that TNF-α and IFN-γ levels were significantly higher in caffeine-treated groups. The findings of the present study unraveled the immune-related mechanisms behind the caffeinated coffee consumption and lower tumor incidence in humans. In conclusion, the blockade of adenosine pathway by caffeine may constitute an effective means to enhance anti-tumor immune response. © 2019